If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = -9x + 7x + 6 Multiply f * x fx = -9x + 7x + 6 Reorder the terms: fx = 6 + -9x + 7x Combine like terms: -9x + 7x = -2x fx = 6 + -2x Solving fx = 6 + -2x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 6x-1 + -2 Simplifying f = 6x-1 + -2 Reorder the terms: f = -2 + 6x-1
| 20=8+36+12x | | -20x^2+15x+64=25 | | =(3r^3)(2t^2)(4r^4) | | 5x+10=4x | | 4log(3x-10)+10=12 | | 9(0.17)+5=4(0.17+2)+5(0.17) | | X^2+7x+12.25=12.25 | | 6n-30-11n=0 | | y=-9x-1 | | 3x-1+12=18 | | 0=-16t^2-5t+100 | | 14x+7y=49 | | 2(-3x+10)+7=12 | | 3*-9*-4= | | 7(x+10)=3x+78 | | 10*3+2(x)=38 | | 4ln(3x-10)+10=12 | | y=2x+98 | | 7x-5=4-2x+3 | | 3x^4-8x^3+6x^2+12x-2=0 | | 7x+45=24 | | 2b-7+4b+b-3b-1= | | 3y+14y-6y-9y+1-y-3y= | | 38+7k=9(k+4) | | 0.75x-6=3 | | -8(6y-4u-5)= | | 11-2n=3 | | (9y-18)+4=31 | | (x+3)2=5 | | 0.003t+1=.22 | | 22=p-12 | | -3(a-4)+9=a+1 |